(untitled) («CONTEMPORARY TECHNOLOGIES OF COMPUTATIONAL LINGUISTICS», 2024)
In this thesis, the types of analysis performed in the process of creating a terminological dictionary, that is, in terminography, as well as the issues of terminology in text analysis are highlighted. Also, the stages of the analysis are considered. The most important linguistic features, which are terminographically significant, have been touched upon.